1989
DOI: 10.1016/0014-5793(89)81509-1
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant core particles of hepatitis B virus exposing foreign antigenic determinants on their surface

Abstract: Insertion of foreign oligopeptide sequences (4G50 amino acids in length) into the Pro144 position of hepatitis B core antigen (HBcAg) leads to the formation of chimeric capsids in Escherichia co/i cells. These capsids are morphologically and immunogically similar to native HBcAg, but expose the inserted oligopeptides on their outer surface and exhibit antigenic and immunogenic characteristics of the latter. As a source of model antigenic determinants, the appropriate DNA copies excised from cloned viral genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…Unexpectedly, we found that at higher concentrations of proteinase K, the capsid signal displayed an upshift pattern. The cause of the shift could be due to the removal of associated proteins from the exterior of the capsid or the cleavage of the C-terminal tail of the core protein, which is believed to extend out from the capsid, at least sometimes (7,45,46). Interestingly, a similar pattern was observed when HBV capsids were treated with SDS.…”
Section: Vol 82 2008 Incorporation Of A3g Into Hbv Nucleocapsids 6857mentioning
confidence: 99%
“…Unexpectedly, we found that at higher concentrations of proteinase K, the capsid signal displayed an upshift pattern. The cause of the shift could be due to the removal of associated proteins from the exterior of the capsid or the cleavage of the C-terminal tail of the core protein, which is believed to extend out from the capsid, at least sometimes (7,45,46). Interestingly, a similar pattern was observed when HBV capsids were treated with SDS.…”
Section: Vol 82 2008 Incorporation Of A3g Into Hbv Nucleocapsids 6857mentioning
confidence: 99%
“…1 In vaccine studies, HBcAg is a potent immunogen even in the absence of adjuvant, and can be used as a carrier molecule for homologueous and heterologous epitopes. [2][3][4][5][6] HBsAg is the antigen used in the commercial recombinant HBV vaccine, which has been proven over the last 20 years to be a very safe and effective prophylactic vaccine against HBV infection. 7 However, there remains a need for development of more potent hepatitis B vaccines, both for use as prophylactic vaccines in poor responders to the current HBV vaccines and for use in therapeutic HBV vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…27 This is related to the ability of HBcAg to act as a potent B-cell activator, enabling activated B cells to work efficiently as primary APC. 4,5 Another explanation for the strong immunogenicity of HBcAg is the presence of nucleic acids bound to the C-terminal region of the HBcAg molecule. These nucleic acids are copurified with HBcAg as a nucleoprotein from Escherichia coli .…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that these pores are essential to allow nucleotides access to the capsid interior during the DNA synthesis and it is also relevant to the reported accessibility of the C-terminal tail to proteinases and antibodies (Machida et al, 1991;Wynne et al, 1999). When the C-terminal region is replaced by foreign inserted sequences, these insertions can be detected by special antibodies on the outside of the assembled capsids (Borisova et al, 1989).…”
Section: Structural Characteristics Of the Capsid Protein Hbcagmentioning
confidence: 99%